(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article is devoted to the history of the study of the phenomenon of application, the views of linguists are discussed, in which the study of the phenomenon of application was carried out, such as G.Ya., Solganik, A.A. Andrievskaya, Sh. Bally, E.A. Referovskaya, M.E. Shafiro and B. Tursunov.